Prevention of Incisional Hernias by Prophylactic Mesh-augmented Reinforcement of Midline Laparotomies for Abdominal Aortic Aneurysm Treatment: A Randomized Controlled Trial. Issue 4 (April 2016) - Muysoms, Filip E.; Detry, Olivier; Vierendeels, Tijl; Huyghe, Marc; Miserez, Marc; Ruppert, Martin; Tollens, Tim; Defraigne, Jean-Olivier; Berrevoet, Frederik
Abstract : Supplemental Digital Content is available in the text Abstract : Background: The incidence of incisional hernias after abdominal aortic aneurysm repair is high. Prophylactic mesh-augmented reinforcement during laparotomy closure has been proposed in patients at high risk of incisional hernia. Methods: A multicenter randomized trial was conducted on patients undergoing elective abdominal aortic aneurysm repair through a midline laparotomy (Clinical.Trials.gov: NCT00757133). In the study group, retromuscular mesh-augmented reinforcement was performed with a large-pore polypropylene mesh (Ultrapro, width 7.5 cm). The primary endpoint was the incidence of incisional hernias at 2-year follow-up. Results: Between February 2009 and January 2013, 120 patients were recruited at 8 Belgian centers. Patients' characteristics at baseline were similar between groups. Operative and postoperative characteristics showed no difference in morbidity or mortality. The cumulative incidence of incisional hernias at 2-year follow-up after conventional closure was 28% (95% confidence interval [CI], 17%–41%) versus 0% (95% CI, 0%–6%) after mesh-augmented reinforcement ( P < 0.0001; Fisher exact test). The estimated "freedom of incisional hernia" curves (Kaplan-Meier estimate) were significantly different across study arms (χ 2 = 19.5, P < 0.0001; Mantel-Cox test). No adverse effect related to mesh-augmented reinforcement was observed, apart from an increased mean time to close the abdominal wall for mesh-augmented reinforcement compared with the control group: 46 minutes (SD, 18.6) versus 30 minutes (SD, 18.5), respectively ( P < 0.001; Mann-Whitney U test). Conclusions: Prophylactic retromuscular mesh-augmented reinforcement of a midline laparotomy in patients with abdominal aortic aneurysm is safe and effectively prevents the development of incisional hernia during 2 years, with an additional mean operative time of 16 minutes.